Three-Dimensional Cobalt Phosphide Nanowire Arrays as Negative Electrode Material for Flexible Solid-State Asymmetric Supercapacitors - Zheng, Zhi; Retana, Michael; Hu, Xiaobing; Luna, Ramona; Ikuhara, Yumi H; Zhou, Weilie (ACS applied materials & interfaces, 2017)
Despite the great progress that has been accomplished in supercapacitors, the imbalance of the development of positive and negative electrode materials still remains a critical issue to achieve high energy density; therefore, exploring high-performance negative electrode materials is highly desirable. In this article, three-dimensional cobalt phosphide (CoP) nanowire arrays were synthesized on a carbon cloth and were utilized as a binder-free supercapacitor negative electrode. The as-synthesized CoP nanowire arrays presented a high capacitance of 571.3 mF/cm2 at a current density of 1 mA/cm2. By using CoP nanowire arrays as the negative electrode and MnO2 nanowire arrays as the positive electrode, a flexible solid-state asymmetric supercapacitor has been fabricated and has exhibited excellent electrochemical performance, such as a high energy density of 0.69 mWh/cm3 and a high power density of 114.2 mW/cm3. In addition, the solid-state asymmetric supercapacitor shows high cycle stability with 82% capacitance retention after 5000 charge/discharge cycles. This work demonstrates that CoP is a promising negative electrode material for high-performance supercapacitor applications.